ANALISIS PENGUASAAN KONSEP IKATAN KIMIA PADA MATA KULIAH KIMIA ORGANIK MELALUI INSTRUMEN TWO TIER - Nurbaity Nurbaity; Ine Mustikasari (LPPM Universitas Negeri Jakarta, 2012)
The research was performed at Chemical Education FMIPA UNJ. The aim of the research was to analyze to understand the chemical bonding concept understanding on Organic Chemistry . The research method was descriptive with research subjects were chemical education students who registered to Organic Chemistry subject at odd semester year 2010/2011. The two tier instrument was applied for this research. Mean while, essay test was used to analyze Organic Chemistry concept understanding. The results showed that student’s concept understanding on chemical bonding was remaining in low level. Approximately 28.50% of students were easy in understanding chemical bonding concept and around 31.50% of students were in misconception in chemical bonding. In addition, students acquired difficulties to understand the chemical bonding concept were about 40.00%. Remedial was take afteranalyzing of chemical bonding concept,help lecturers in planning and teaching effective Organic Chemistry Lesson. Key work ; Chemical bonding , two tier instrument Abstrak Penelitian ini dilakukan di Program Studi Pendidikan Kimia FMIPA UNJ dengan tujuan menganalisis penguasaan konsep ikatan kimia pada mata kuliah kimia organik. Metode penelitian adalah metode deskriptif, subjek penelitian mahasiswa Pendidikan Kimia yang mengambil mata kuliah kimia organik I pada semester ganjil tahun ajaran 2010/2011. Instrumen yang digunakan adalah instrumen two tier untuk menganalisis penguasaan konsep mahasiswa pada ikatan kimia dan tes materi kimia organik menggunakan tes essai. Hasil penelitian menunjukkan bahwa penguasaan konsep mahasiswa pada materi ikatan kimia masih rendah, sekitar 28,50% mahasiswa yang memahami konsep ikatan kimia, 31,50% yang mengalami miskonsepsi, dan mengalami kesulitan sekitar 40%. Pemberian pemantapan setelah menganalisis penguasaan pada materi ikatan kimia membantu dosen dalam merencanakan dan melaksanakan pembelajaran kimia organik yang efektif. Kata kunci : Ikatan kimia, instrumen two tier